Application of meticulous nursing in fluid management of a patient with chronic heart failure (1例慢性心力衰竭患者容量管理的精细化护理体会) - WANG Fangfang (王芳芳); WEN Jie (文杰) (Association of Integrative Nursing, 2023)
This paper summarized the meticulous nursing in fluid management of a patient with chronic heart failure. Meticulous nursing interventions of fluid management including limiting salt intake, patterns of fluid intake, usage of diuretics, monitoring of body weight and urine volume, edema care, psychological care and exercise guidance. Meticulous nursing of fluid management was carried out to make an active participation in self-management, and improve the cardiac function and quality of life. (本文总结1例慢性心力衰竭患者容量管理的精细化护理经验。针对患者进行限盐、液体摄入方式、利尿剂应用方式、体质量及尿量监测、水肿护理、心理干预、运动指导等精细化容量管理方式, 使患者主动积极参与自我管理, 改善患者心功能, 提高患者生活质量。)